Comparison of Anisotropic Diffuse Sky Radiance Models for Irradiance Estimation on Building Facades. (2017) - Li, Zhengrong; Xing, Haowei; Zeng, Shiqin; Zhao, Jinpeng; Wang, Ting
Abstract: With the urban development, complex urban structure and variable sky radiance distribution lead to unpredictable solar energy, especially diffuse radiance, on building facades. Accurate irradiance estimation based on diffuse sky radiance models is required for high performance building design and use. A comparison is presented of seven anisotropic distribution models for sky diffuse radiance: Bugler model, Klucher model, Skartveit model, Perez model, Muneer model, Yao model and Igawa model. Their performance was judged against measurement data from the aspect of orientations and sky conditions. On the whole, it suggests that Iwaga model, which is based on continuous distribution functions and all-weather conditions, should be implemented to estimate diffuse irradiance on building facades in Beijing.